Effect of dietary supplementation of humic acids on performance of broilers - NAGARAJU, R; REDDY, B S V; GLORIDOSS, R; SURESH, B N; RAMESH, C (The Indian Journal of Animal Sciences, 2014)
An experiment was conducted to study the efficacy of humic acid (HA) based product as a substitute for antibiotic in broilers. Two basal diets, viz. moderate (BIS 1992) and low nutrient density diets (3.5% lesser ME and CP than BIS 1992 specification) were formulated. Low and moderate nutrient density basal diets without antibiotic were served negative controls and with added antibiotic became positive controls. Further, moderate and low nutrient density diets were supplemented with 0.5, 0.75 or 1g HA based product per kg of feed to result in 6 test diets. Each of such diets prepared for starter (0–14 days), grower (15–28 days) and finisher (29–42 days) phases were offered to duplicate groups of 14 chicks each. The results revealed significantly higher body weight gains in moderate density diet with 0.1% HA during starter phase, more feed consumption in low nutrient density diet with 0.075% HA during finisher stage and better feed efficiency in moderate density diet with 0.075% HA. However, the cumulative body weight gain, feed consumption and feed efficiency including net returns were comparable among different treatments during 42–day trial. Metabolizability of dry matter and crude protein was significantly high in groups fed moderate nutrient density diet than low nutrient density diets however, no definite trend was observed with HA supplementation. At the termination of 42–day-trial, no significant differences were observed in dressing percentage, breast-meat yield, abdominal fat pad, relative weights of liver, heart, gizzard, spleen and bursa among different treatments. On 10-day post-vaccination, the ND titer values were statistically similar among different treatments while improved IBD titer values of birds were observed in HA supplanted groups. It was concluded that the addition of HA up to 0.1% particularly in the low nutrient density antibiotic free diets can improve the performance and immune status of broilers without affecting their carcass characteristics.